2011
DOI: 10.1002/ijc.26440
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic PIK3CA mutations in colorectal cancers and polyps

Abstract: Oncogenic PIK3CA mutations contribute to colorectal tumorigenesis by activating AKT signaling to decrease apoptosis and increase tumor invasion. A synergistic association of PIK3CA mutation with KRAS mutation has been suggested to increase AKT signaling and resistance to antiepidermal growth factor receptor inhibitor therapy for advanced colorectal cancer, although studies have been conflicting. We sought to clarify this by examining PIK3CA mutation frequency in relation to other key molecular features of defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 33 publications
8
73
2
1
Order By: Relevance
“…Although previous studies have investigated the role of the PIK3CA mutation and gene methylation in CRC, the data are inconclusive. Certain studies reported a significantly higher frequency of the PIK3CA mutation in the CpG island methylator phenotype (CIMP)-high tumor compared with CIMP-negative tumors and a significant correlation between the PIK3CA mutation and RASSF2 gene methylation (29,32,33), whereas other studies failed to observe this correlation (11,34). In the present study, although CIMP status was not examined, the PIK3CA mutation did not exhibit an association with the methylation status of the genes examined.…”
Section: Discussioncontrasting
confidence: 74%
“…Although previous studies have investigated the role of the PIK3CA mutation and gene methylation in CRC, the data are inconclusive. Certain studies reported a significantly higher frequency of the PIK3CA mutation in the CpG island methylator phenotype (CIMP)-high tumor compared with CIMP-negative tumors and a significant correlation between the PIK3CA mutation and RASSF2 gene methylation (29,32,33), whereas other studies failed to observe this correlation (11,34). In the present study, although CIMP status was not examined, the PIK3CA mutation did not exhibit an association with the methylation status of the genes examined.…”
Section: Discussioncontrasting
confidence: 74%
“…Two recent studies on stage I-IV colorectal cancers have suggested that exon 20 mutations correlate more strongly with BRAF mutation, CIMP-high/-low (CIMP-H/-L) and MSI-H status (31,32), and one reported that exon 9 mutations may more closely associate with KRAS mutation (31,32). The latter has further been observed in a study on metastatic colorectal cancer (30).…”
Section: Introductionmentioning
confidence: 84%
“…39) and Whitehall and colleagues (31)]. The 8 most numerous states plus an omnibus state consisting of the remaining genotypes were modeled using mixed effects logistic regression or, alternatively, a 3-stage hierarchical multinomial-Dirichlet model.…”
Section: Integrated Analysis Of Pik3ca Exon 9 and 20 Mutations For CLmentioning
confidence: 99%
See 2 more Smart Citations